(untitled) (PIONIR: JURNAL PENDIDIKAN, 2023)
This study aims to reveal (1) the effect of a work commitment on teacher performance; (2) the effect of job satisfaction on teacher performance. This research was conducted at public elementary schools in the city of Banda Aceh. The study population was all public elementary school teachers in the city of Banda Aceh totaling 481 people. Determination of the sample using the Slovin formula, with a total sample of 218 people. Data was collected using a questionnaire which was filled in by respondents who came from teachers. Research analysis using descriptive analysis and inferential analysis with path analysis (path analysis). The research results show that:; (1) Work commitment has a significant influence on teacher performance, it is shown that ρ31 = 0.334; (2) Job satisfaction has a significant influence on teacher performance and it is shown that ρ32 = 0.268. The teacher performance model found in this study explains that improving teacher performance can be done through work commitment and job satisfaction which will directly lead to better teacher performance.